Oxidative stress injury in doxorubicin-induced cardiotoxicity - Songbo, Mei; Lang, Hong; Xinyong, Cai; Bin, Xiao; Ping, Zhang; Liang, Shao (Toxicology letters, 2019)
Doxorubicin (DOX) is widely used as a broad-spectrum anti-tumor anthracycline to treat various cancers. The serious adverse effects of DOX on cardiotoxicity limit its clinical application. There are several different mechanisms involved in DOX-induced cardiotoxicity. Oxidative stress (OS) is caused by an imbalance between reactive oxygen species (ROS) and endogenous antioxidants in response to injury, which can lead to myocardial toxicity. The aim of this review was to investigate the mechanisms underlying the effects of oxidative stress injury on myocardial toxicity, from three different aspects: the increase in downstream oxidative stress products, the reduction in upstream antioxidative stress products, and subcellular organelles. Finally, there are some anti-oxidative drugs that show efficacy in limiting DOX-induced cardiotoxicity. It is necessary to fully understand the toxicity of DOX to the myocardium and achieve symptomatic treatment.